PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR IPA KELAS IV SD - Dewana, Aditya (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
Â Abstract The problem in this research is whether there is influence and how big the influence model of Problem Based Learning towards a learning outcomes The Nature Of Science students in class IV elementary school 12 South Pontianak Country?. This research aims to demonstrate the influence and how big the influence model of Problem Based Learning towards a learning outcomes IPA students in class IV elementary school the country 12 South Pontianak. This research uses experimental methods. Experimental research on form used is a quasi experimental design with Nonequivalent Control Group Design types. The population in this research is the whole grade IV elementary school 12 South Pontianak Country consisting of 50 students. The techniques used in the collection of data is the measurement techniques. Data collecting tool used is reserved in the form of 25 multiple choice question. Research results are obtained, the average value of the post-test control class of 67.50 and average value of post-test experimental 77.4 class. Based on the analysis of the hypothesis test using the test-t obtained t_hitung = 2.314 and substitute price t_tabel (Î± = 5%) of 2.021, which means t_hitung (2,314) > t_tabel (2,021), the Ha received and the calculation of effect size obtained ICE of 0.75. So, it can be concluded that there is a Problem Based Learning model of influence against the results of learning The Nature Of Science students in class IV elementary school 12 South Pontianak with medium categories. Keywords : Influence, Problem Based Learning, Learning Outcomes, The Nature Of Science.